KUALITAS AUDIT DAN AUDIT TENURE - Reygen Pramana Jati (Jurnal Riset Akuntansi dan Keuangan, 2014)
Audit quality is determined by auditor’s competence to find misstatements in financial report and report the findings in the audit report that makes auditor’s independency strongly affect audit quality, in addition to auditor’s competency in performing their duties. Auditor’s independency is related to lengthy audit engagement with client. This study aims to obtain empirical evidence about the influence of lengthy audit engagement to audit quality. Based on the literature review, the hypothesis proposed in this study is the length of the audit engagement negatively affects audit quality. This study uses earnings benchmarks as proxy of audit quality developed from Carey and Simnett (2006). To test the hypothesis, an empirical model was developed and tested with binary logistic regression technique. Empirical test results indicate a significant negative influence of lengthy audit engagements to audit quality. It means that lengthy audit engagement deteriorates audit quality, indicated by the failure to meet earnings benchmark. Keywords: Audit Tenure, Audit Quality, Earnings Benchmark